Determinant of Poverty Rates in Indonesia: A Panel Data Regression Analysis - Kharisma, Safa; Maulida, Salva Putri; Caesarani, Yesa (Journal of Policy and Sustainable Development Studies, 2026)
Poverty is a deeply complex and multidimensional phenomenon that has become a central concern for the Indonesian government. According to data from the Central Statistics Agency (BPS), the poverty rate in Indonesia increased significantly from 9.41% in 2019 to 9.78% in 2020, and further rose to 10.14% in 2021. This study aims to examine the key determinants influencing poverty rates in Indonesia, with the ultimate goal of formulating effective policy interventions to alleviate poverty. Employing a quantitative research approach using panel data regression, the study utilises secondary data from BPS spanning the period of 2019 to 2023. The dependent variable is the poverty rate, while the independent variables include economic growth, literacy rate, average years of schooling, open unemployment rate, and the Human Development Index (HDI). The findings reveal that increases in HDI, economic growth, literacy levels, and the open unemployment rate are associated with reductions in poverty. Interestingly, an increase in the average years of schooling correlates with a rise in poverty levels, presenting a paradox that warrants further investigation.